Analisis Inovasi Desa Mandiri Di Kecamatan Tellu Limpoe Kabupaten Sinjai - Muhlis Muhlis; Mochamat Nurdin; Fitrawati AB (Universitas Mbojo Bima, 2025)
Abstract. This study aims to analyze independent village innovation in Tellu Limpoe District, Sinjai Regency, focusing on three villages, namely Sukamaju Village, Kalobba Village, and Pattongko Village. The analysis was conducted based on four main indicators of innovation diffusion theory: innovation, communication channels, timeframe, and social systems. This study uses qualitative research methods with data collection techniques through in-depth interviews, participatory observation, and documentation studies. The data analysis techniques used by the author are data reduction, data presentation, and conclusion drawing. The results of the study show that the three villages have different innovation characteristics in an effort to achieve village independence. In terms of innovation indicators, the three villages have succeeded in implementing innovative programs that have never existed before, especially in the fields of agriculture, fisheries, community empowerment, management of BUMDes, and information technology innovation implemented through digital administration systems and the application of Appropriate Technology. From the communication channel aspect, building an integrated communication system that combines modern technology and traditional techniques. In terms of timeframe, the analysis shows that planned and implemented village innovations can achieve the planned targets according to the specified timeline, both in the short, medium, and long term. From a social system perspective, the community structure in Tellu Limpoe District, which is still strongly imbued with the values ​​of mutual cooperation, has a significant influence on the success of innovation implementation. The main supporting factors for innovation success are transformational leadership, community participation, and synergy with external parties. Meanwhile, limited human resources, infrastructure, lack of ongoing technical assistance, and resistance to change are the main inhibiting factors.